Management Of A Radicular Cyst With Synthetic Bone Graft Subtitute (Case Report) - Fisna Melia (Cakradonya Dental Journal, 2014)
The radicular cyst has been classified as inflammatory cyst, as a consequence to pulpal necrosis following caries, with an associated periapical inflammatory response. Many times it is difficult to differentiate periapical cysts from the obligatory pre-existing chronic periapical periodontitis lesions radiographically. This paper presents a case of radicular cyst in the maxillary anterior region and removal of the cyst followed at all times with the laying of a bone graft substitute in which the defectarea.